The effect of tethered swimming speed on external power output of well-trained disabled swimmers - Lee, C. J; Payton, C. J (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION:Measuring propulsive force (Fp) and external power output (Pext) during swimming is exceptionally difficult due to the continual displacement of water. Tethered swimming is a highly reliable method of measuring Fp and presents a strong relationship with swimming performance. Due to advances in technology, tethered swimming can be adapted so that tether force is recorded as the swimmer progresses down the pool, allowing for the further calculation of power. The aim of the study was to examine the effect of tether speed on Pext and to identify the speed at which swimmers with a disability produce their peak power output (PPext). METHODS: Eight male and thirteen female swimmers with an IPC physical impairment classification ranging from S5 to S10, participated in the study. External power output was measured using a semi-tethered device which restricted the swimmer to a pre-set constant speed, whilst simultaneously measuring the tether force produced. Swimmers performed six maximal effort, short duration (<10 s) front crawl swims at tether speeds ranging from 30 - 80% of their maximal swimming speed (SSmax). RESULTS: As tether speed increased, the tether force decreased. External power output (mean tether force × tether speed) increased to a maximum (PPext) at either 50% or 60% of SSmax, after which power then decreased. A significant correlation was found between PPext and SSmax (r =0.85; p<0.01). The less physically impaired swimmers (S8-S10) produced higher power scores (48.6 ± 24.0 W) than the more physically impaired S5-S7 swimmers (31.4 ± 13.3 W). The highest and lowest PPext scores were 19.0 W and 96.9 W, respectively. There was a significant relationship between IPC classification and PPext in both the male (r =0.89; p<0.01) and female(r =0.75; p<0.01) groups. DISCUSSION: As the external power Pext is the product of the tether force and the speed of the swimmer, it does not account for the power required to overcome drag or the power loss to the water. Nevertheless, an improvement in Pext, at any given test speed, indicates that a swimmer has increased their propulsive force production or decreased their drag. The six-speed test identifies the PPext for each individual swimmer and appears to discriminate between impairment classes. It is believed that this test may be a useful tool for monitoring power development in swimmers and may also have future applications in the IPC classification process.